Genetic and Phenotypic Characteristics of the Salmo trutta Complex in Italy - Edo D’Agaro; PierPaolo Gibertoni; Fabio Marroni; Maria Messina; Emilio Tibaldi; Stefano Esposito (Applied Sciences, 2022)
Salmonid fish have become ecological and research models of study in the field of conservation genetics and genomics. Over the last decade, brown trout have received a high level of interest in research and publications. The term Salmo trutta complex is used to indicate the large number of geographic forms present in the species Salmo trutta. In Europe, the S. trutta complex consists (based on mitochondrial DNA control region analysis) of seven major evolutionary lineages: Atlantic (AT), Mediterranean (ME), Adriatic (AD), Danubian (DA), Marmoratus (MA), Duero (DU) and Tigris (TI). In several nations, the difficulty of identifying some lineages derives from their wide phenotypic and geographic plasticity and the presence of mixed lineages (due to introgressive hybridization with domestic AT populations). In Italy, the S. trutta complex populations living in the Tyrrhenian area and on the main islands (Sicily, Sardinia and Corsica) showed high genetic diversity. Currently, on the Italian Red List, the protected (near threatened) populations are the AD and ME lineages. Recent studies based on traditional (mitochondrial and nuclear markers) and NGS (next-generation sequencing) analyses have clarified some genetic differences between the populations of the Tyrrhenian region, Sicily, Sardinia and Corsica. Native populations in Sardinia belong to the AD lineage, while those living in Corsica are mainly characterized by the AD, MA and ME haplotypes. In Sicily, in the area of the Iblei mountains, an AT lineage (North African) exists. According to some authors, the term Salmo macrostigma should only be used for populations in North Africa. The use of genotyping methods based on mtDNA and nuclear markers and the latest generation sequencing techniques can improve the study of populations and evolutionary lineages in areas where there are overlaps and hybridization phenomena.